The living will: Patients should be informed of the risks. Issue 2 (25th January 2021) - Kurin, Michael; Mirarchi, Ferdinando
Abstract: Living wills are designed to ensure that patients' preferences will be respected at the end of life should they lose capacity to make decisions. However, data on living will use suggest there are barriers to achieving this objective. Moreover, there is evidence that completion of a living will creates a risk of an unwanted outcome: the potential for premature withdrawal of interventions. We suggest a multifaceted approach to improve the ability of living wills to achieve their goals. However, acknowledgment of the current reality should oblige providers offering a living will to their patients to present a balanced view of living wills that includes enumeration of the risk, barriers to achieving the purported benefits, and alternatives to completing a living will, in addition to discussion of the potential benefits. This requires a change in current practice that would encourage shared decision making regarding whether completing a living will or other type of advance directive is desired by the patient and discourage the proliferation of living wills completed without providing these important advantages and disadvantages to the patient.